1967
DOI: 10.1042/bj1050181
|View full text |Cite
|
Sign up to set email alerts
|

A determination of the sub-units of arachin by osmometry. Arachins A, B and A1

Abstract: 1. Osmotic pressure determinations of dissociated arachins are a particularly suitable method for determination of the number of sub-units in the protein, because they yield a number-average molecular weight. 2. Arachin, in 8m-urea-0.1m-sulphite, produces 12 sub-units from the form of molecular weight 345000. 3. When the urea concentration is varied the molecules became fully dissociated at 6m-urea-0.1m-sulphite. Although sulphite is necessary to break disulphide bridges, concentrations greater than 0.1m cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1973
1973
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(16 citation statements)
references
References 8 publications
1
15
0
Order By: Relevance
“…As reported hy Dawson (19711, Tombs (1963, 1965, and Tombs and Lowe (1967), these data confirm that the peanut reserve proteins are primarily arachin and conarachin, which are themselves made up of smaller suhunits difficult to separate by the usual fractionation procedures. An attempt to further isolate and characterize the proteins within the conarachin and arachin fractions follows.…”
Section: Resultssupporting
confidence: 85%
“…As reported hy Dawson (19711, Tombs (1963, 1965, and Tombs and Lowe (1967), these data confirm that the peanut reserve proteins are primarily arachin and conarachin, which are themselves made up of smaller suhunits difficult to separate by the usual fractionation procedures. An attempt to further isolate and characterize the proteins within the conarachin and arachin fractions follows.…”
Section: Resultssupporting
confidence: 85%
“…Monterio and Prakash (1994) observed the subunit pattern of arachin to contain seven bands of molecular weights from 15,800 to 72,400 Da, but six of them were prominent. Tombs and Lowe (1967) also reported six major subunits and classified them into two groups of hydrophilic and hydrophobic subunits. It is known that proteins derived from different peanut species exhibit different behavior in the dissociation-association properties of the arachin molecular.…”
Section: Sds-pagementioning
confidence: 96%
“…6). Tombs and Lowe (1967) observed the subunit pattern of arachin and reported that it contained six major subunits and classified them into two groups of hydrophilic and hydrophobic groups. Monteiro and Prakash (1994a, b) reported seven bands having molecular weights ranging from 158,000 to 72,400 Da and also showed that six prominent bands had molecular weights of 72,400, 60,300, 39,800, 33,100, 26,900 and 21,900 Da.…”
Section: Gel Electrophoresis Of Enzyme Hydrolysed Arachinmentioning
confidence: 98%